2010
DOI: 10.1149/1.3486095
|View full text |Cite
|
Sign up to set email alerts
|

Unstructured Pore Network Modeling with Heterogeneous PEMFC GDL Porosity Distributions

Abstract: This is the first investigation of the liquid water saturation profile dependence on empirically determined heterogeneous polymer electrolyte membrane fuel cell ͑PEMFC͒ gas diffusion layer ͑GDL͒ porosity distributions. An unstructured, two-dimensional pore network model using an invasion percolation algorithm is presented. Random fiber placements are based on the heterogeneous porosity distributions of six commercially available GDL materials recently obtained through X-ray-computed tomography visualizations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 35 publications
(80 reference statements)
2
81
0
Order By: Relevance
“…All parameters including number injection points and pore size distribution were consistent between two cases. The details on generating a pore network and performing invasion-percolation algorithm were described by Hinebaugh et al 28 According to the simulation, the 50-μm MPL pertained to four individual clusters, each with a breakthrough location, while the 150-μm MPL had only two. Moreover, it is shown that the total content of water increases with a thicker MPL, because greater number of pores must be occupied for breakthrough compared to a thinner MPL.…”
Section: Discussionmentioning
confidence: 99%
“…All parameters including number injection points and pore size distribution were consistent between two cases. The details on generating a pore network and performing invasion-percolation algorithm were described by Hinebaugh et al 28 According to the simulation, the 50-μm MPL pertained to four individual clusters, each with a breakthrough location, while the 150-μm MPL had only two. Moreover, it is shown that the total content of water increases with a thicker MPL, because greater number of pores must be occupied for breakthrough compared to a thinner MPL.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental data are 3D microscopic liquid water distributions from water injection experiments obtained by X-ray tomographic microscopy [11]. X-ray tomography has been used in several works to visualize liquid water in GDLs [23,24,43e49].…”
Section: Introductionmentioning
confidence: 99%
“…As for the present work, many of these studies are based on pore network models (PNM) (e.g., Sinha and Wang 2007;Markicevic et al 2007;Bazylak et al 2008;Hinebaugh et al 2010;Lee et al 2009Lee et al , 2010Lee et al , 2014Gostick 2013;Wu et al 2013;Fazeli et al 2015;Quin 2015).…”
Section: Literature Reviewmentioning
confidence: 99%